2014
DOI: 10.1074/jbc.m114.551408
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Screen for Candidate Antimalarials Targeting Plasmodium Kinesin-5

Abstract: Background:The genome of the major malaria parasites encodes a single Kinesin-5 homolog. Results: MMV666693 is a selective allosteric inhibitor of Plasmodium Kinesin-5. Conclusion: Plasmodium Kinesin-5 is druggable and susceptible to allosteric inhibition. Significance: This is the first demonstration of allosteric control of a non-human Kinesin-5 by a small chemical and opens the door to new antimalarials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Although the exact molecular basis of these functions remains controversial, Kinesin-8s modulate MT dynamics and may either stabilise, destabilise, slow growth, or actively depolymerize MTs in spindle function [18,19,47]. Phylogenetic analysis showed that while there are 9 kinesin genes in Plasmodium, a number of kinesin classes, typically involved in long-distance intra-cellular transport in metazoa, such as kinesin-1 and kinesin-3, are absent [3,37]. proteins will be the topic of future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact molecular basis of these functions remains controversial, Kinesin-8s modulate MT dynamics and may either stabilise, destabilise, slow growth, or actively depolymerize MTs in spindle function [18,19,47]. Phylogenetic analysis showed that while there are 9 kinesin genes in Plasmodium, a number of kinesin classes, typically involved in long-distance intra-cellular transport in metazoa, such as kinesin-1 and kinesin-3, are absent [3,37]. proteins will be the topic of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses have identified 9 kinesin genes in the Plasmodium genome [2,3,37] though not much is known in other members of the group Apicomplexa. Here 7 we have analysed a high-resolution representation of the phylogenetic distribution of kinesins in all known Apicomplexa including Plasmodium.…”
Section: Introductionmentioning
confidence: 99%
“…Steady state kinetics of Eg5 were monitored using a NADH coupled enzymatic assay ( 46 , 71 ) in a SpectraMax M2e spectrophotometer (Molecular Devices) in 96-well plate format ( 47 ). In measurements of basal ATP hydrolysis rates in the presence of saturating 1 m m MgATP, motor protein concentration was as follows: L263F and T100C/L263F, 0.625 μ m ; T100C and Y82A, 1.5 μ m ; WT, Q78A, M115A, L263A, M115A/L263A, M115I/L263F, P137A, V298C, and P137A/V298C, 2.5 μ m ; and R138A, M115I, Q78N, Y82F, R138L, Q78A/R138A, and Y82F/T100C, 5 μ m .…”
Section: Methodsmentioning
confidence: 99%
“…The large family of kinesins includes molecular motors that are essential for several processes during cell division [28,29], and in Plasmodium berghei there are nine kinesin genes, including two kinesin-8 genes that are important in cell division and male gamete formation [23,30]. There is a single Plasmodium kinesin-5, and since this protein plays an important role during cell proliferation in many eukaryotes, and is considered as a strong target for the development of therapeutics against many diseases including malaria [31], we decided to study its role during cell division in the malaria parasite.…”
Section: Introductionmentioning
confidence: 99%